(untitled) (FULafia Journal of Science and Technology, 2019)
Population projection has been a good alternative to real population census in under-developing country like Nigeria. This study project twenty-five (25) years of Nigeria population between 2006 and 2031. We used Malthus model equation for the projection population using 2006 conducted Nigeria census as initial population. We employed two numerical techniques: Exponentially collocation approximation method and Differential Transformation method to solve Malthus model for the year under consideration. The projected Nigeria population for twenty-five (25) years obtained are in complete agreement with the analytical solution of Malthus model.